Innovative Integrated Jet Grout And Contiguous Cfa Piled Solution For Complex Deep Shoring Wall In Soft Soils – Retaining Structural Design And Analysis - W. L. Chong; Y. Zou (Deep Foundations Institute, 2022)
There are many types of Earth Retention Systems (ERS) available in the market where more than one method can be a feasible solution for a project. This paper examines the design and construct process of a project in Dee Why, NSW using a hybrid ERS comprising contiguous piles with jet grout infill. The development comprises a deep basement and mixed-use urban superstructure. The site is located in an area of variable ground conditions, high ground water table and in proximity to existing buildings with multi-level basements. This paper details a comprehensive assessment of the geological conditions and strategies adopted to better understand the effectiveness of the proposed product and to minimise the associated risks of the proposed solution. This involved conducting additional geotechnical investigation, extensive numerical modelling and in-situ monitoring of the movements and the performance of the walls. A monitoring regime consisting of inclinometers, survey points on capping beam and prisms on the neighbouring buildings and roads surrounding shoring wall was implemented. The monitoring results were back-analysed using computer software WALLAP, Plaxis–2D and Plaxis–3D for the post-construction examinations. This paper details the effectiveness and advantages of a hybrid ERS using contiguous piles with jet grout infill.